PENGARUH SEMANGAT KERJA, KEJELASAN PERAN, FISIK LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI UNIVERSITAS POTENSI UTAMA - Austin Alexander Parhusip (Jurnal Prodi Fakultas Ekonomi-UISU, 2019)
An organization is established because it has goals that it wants and must achieve. The importance of the role of human resources in educational institutions, human’resources’should be managed properly. Managing human resources is the duty of a manager. The word